Gonadal pathogenicity of an infectious bronchitis virus strain from the Massachusetts genotype - Pereira, Nicole Assis; Alessi, Antônio Carlos [UNESP]; Montassier, Hélio José [UNESP]; Pereira, Ricardo José Garcia; Taniwaki, Sueli Akemi; Botosso, Viviane Fongaro; Rui, Bruno Rogério; Richtzenhain, Leonardo José (Springer Nature, 2019)
An outbreak of infectious bronchitis caused by the IBVPR03 strain of the Massachusetts genotype affected H-120 vaccinated laying hens in South Brazil. We investigated the cross protection of the vaccine by assessing the traqueal ciliostasis, virus recovery, and histopathological changes typically observed in the respiratory tract. Although the IBVPR03 strain is S1-genotyped as Massachusetts with a high genomic similarity to the H-120 vaccine strains, surprisingly, we found no tropism or pathogenicity to the trachea in birds infected with this strain. On the other hand, we observed ovarian and testicle lesions. Here, we show that, despite belonging in the Massachusetts genotype, the IBVPR03 pathotype differs from the expected respiratory pattern, causing instead marked histopathological changes in the gonads, so far not associated with this group.
Keywords: Gonadal pathogenicity; Infectious bronchitis virus; Ovaries; Testis; Young chicks